Essay: Family Law and Civil Union Partnerships - Status, Contract and Access to Symbols - Austin, Graeme W (Victoria University of Wellington Law Review, 2006)
This essay locates New Zealand’s civil union legislation within the dynamic between "status" and "contract" that animates modern family law. "Status" concerns who we are; "contract" concerns the transactions we can enter. Because family law is concerned with affective relationships, it cannot apprehend people only as the atomised individuals anticipated by the modernist emphasis on contractual relations. Family law acknowledges the relevance to legal issues of "messy" issues of personality. Among the most complex and powerful aspects of personality with which the law concerns itself is love. Love affects who we are and law affects what love can be. Law provides and constrains the symbolic repertoire that helps organise the way we think about our affective relationships. The enactment of civil union legislation was an enormously positive step. However, by continuing to deny homosexuals the ability to marry, the New Zealand state persists in denying homosexuals a key part of the symbolic repertoire that is relevant to the way people in love can conceptualise their relationships. The transactions the state permits us to enter, particularly transactions that are expressions of love, affect the construction of our identities, illustrating once again the deep links that exist between who we are and the contracts we can enter.